Interactive Screen Media Use by Young Children. Issue 2 (March 2016) - Beal, Judy A.
Abstract : How much screen time is too much? What should nurses tell parents when they ask about their children's use of electronic devices? Our pediatric nursing expert, Dr. Beal covers the latest news from the literature and the American Academy of Pediatrics on how to advise families on media use.